2011
DOI: 10.1103/physrevb.84.054401
|View full text |Cite
|
Sign up to set email alerts
|

First-principles investigation of the very large perpendicular magnetic anisotropy at Fe|MgO and Co|MgO interfaces

Abstract: The perpendicular magnetic anisotropy (PMA) arising at the interface between ferromagnetic transition metals and metallic oxides was investigated via first-principles calculations. In this work very large values of PMA, up to 3 erg/cm 2 , at Fe|MgO interfaces are reported, in agreement with recent experiments. The origin of PMA is attributed to overlap between O-p z and transition metal d z 2 orbitals hybridized with d xz(yz) orbitals with stronger spin-orbit coupling-induced splitting around the Fermi level f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

29
398
2
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 608 publications
(431 citation statements)
references
References 49 publications
29
398
2
2
Order By: Relevance
“…However, at this stage, one cannot totally discard the idea that the corresponding perpendicular magnetic anisotropy arises, in part, from the contribution of an out-of-plane pure interfacial anisotropy between epitaxial MgO and Fe layers as argued by Yang et al in a recent paper. 79 Nevertheless, the relatively low value (7%) of the EL circular polarization measured compared to the spin polarization of Fe (about 40%) can be understood as coming from a certain discontinuity of the Fe layer on MgO owing to nonperfect epitaxial growth, leading to paramagnetic islands. This is supported by the decrease of the polarized EL signal which disappears over 70 K (not shown).…”
Section: Interlayer Exchange Coupling and Spin Injection Problemmentioning
confidence: 99%
“…However, at this stage, one cannot totally discard the idea that the corresponding perpendicular magnetic anisotropy arises, in part, from the contribution of an out-of-plane pure interfacial anisotropy between epitaxial MgO and Fe layers as argued by Yang et al in a recent paper. 79 Nevertheless, the relatively low value (7%) of the EL circular polarization measured compared to the spin polarization of Fe (about 40%) can be understood as coming from a certain discontinuity of the Fe layer on MgO owing to nonperfect epitaxial growth, leading to paramagnetic islands. This is supported by the decrease of the polarized EL signal which disappears over 70 K (not shown).…”
Section: Interlayer Exchange Coupling and Spin Injection Problemmentioning
confidence: 99%
“…A few theoretical groups also addressed Fe/MgO and FeCo/MgO interfaces and have argued that the PMCA of the Fe(001) film is enhanced by the hybridization of Fe 3d orbitals with O p z . 6,7 Nevertheless, recent experiments on TMs/FeCoB/MgO revealed evidence that the role of 5d or 4d orbitals is more decisive; in other words, that the 5d (4d) TMs/CoFeB interface is the origin of the observed PMCA. 8,9 On the other hand, the magnetism in multilayers of 4d and 5d TMs grown on body-centered cubic (bcc) Fe substrate has been a long-standing subject of both experiment [10][11][12][13][14][15] and theory.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it was also shown that in the case of a non-perfect interface (over-or underoxidized), the PMA amplitude is decreasing. 26 This is due to the disappearance of the d z 2 hybridized states around the Fermi level in the presence or absence of an additional oxygen atom at the interface.…”
mentioning
confidence: 99%
“…27 These interfaces contain a number of imperfections including oxygen defects, which according to Yang et al, 26 weaken the out-of-plane magnetic anisotropy. When more layers are added, the subsequent interfaces show perfect atomic arrangement with sharp atomic interfaces.…”
mentioning
confidence: 99%
See 1 more Smart Citation